1985
DOI: 10.7326/0003-4819-102-1-49
|View full text |Cite
|
Sign up to set email alerts
|

Anorexia Nervosa and Sudden Death

Abstract: Necropsy findings and electrocardiograms from three women with anorexia nervosa were reviewed. Necropsy examination failed to establish an anatomic cause of death. Electrocardiograms recorded days or less before death showed various degrees of Q-T interval prolongation: Q-T intervals corrected for heart rate measured 0.61 s, 0.47 s, and 0.46 s, respectively. Terminal ventricular tachyarrhythmias were documented in two patients, including torsade de pointes in one. The necropsy and clinical findings in these th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
92
1
10

Year Published

1986
1986
2006
2006

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 276 publications
(105 citation statements)
references
References 24 publications
1
92
1
10
Order By: Relevance
“…Normal corrected QTc intervals are <0.44 s. 4 The issue of prolongation of the QTc interval has received a great deal of attention because of its association with sudden ventricular arrhythmias and death in adults who lost weight rapidly through a liquid protein modified fast or AN. 2 Lupoglazoff et al 6 found prolongation of the QTc interval (QTc > 0.44 ms) in 25% of adolescents with AN. Another study 1 found that 32% of adolescents with AN had a prolonged QTc, although prolongation was defined as >0 .425 s and there were no controls for comparison.…”
Section: Debra K Katzman Md* Abstractmentioning
confidence: 97%
See 1 more Smart Citation
“…Normal corrected QTc intervals are <0.44 s. 4 The issue of prolongation of the QTc interval has received a great deal of attention because of its association with sudden ventricular arrhythmias and death in adults who lost weight rapidly through a liquid protein modified fast or AN. 2 Lupoglazoff et al 6 found prolongation of the QTc interval (QTc > 0.44 ms) in 25% of adolescents with AN. Another study 1 found that 32% of adolescents with AN had a prolonged QTc, although prolongation was defined as >0 .425 s and there were no controls for comparison.…”
Section: Debra K Katzman Md* Abstractmentioning
confidence: 97%
“…One third of the deaths in adults with eating disorders are due to cardiac complications. 2 There are no such data regarding adolescents with AN.…”
Section: Cardiovascular Complicationsmentioning
confidence: 99%
“…Uma restrição calórica importante reduz a taxa metabólica e provoca alterações nos sistemas músculo-esquelético 23,30,58,59 , cardiovascular 14,37,53,60,61 , endócrino 35,[62][63][64] , termorregulatório 14 e outros [11][12][13]35,65,66 . A anorexia nervosa é o extremo do comportamento restritivo alimentar, no qual o indivíduo se vê como acima do peso, mesmo que esteja 15% abaixo do peso corporal ideal.…”
Section: Comportamentos Alimentares Inadequadosunclassified
“…Os distúrbios de alimentação são doenças crônicas com seqüelas importantes dos pontos de vista clínico e psicológico. Entre elas temos a depressão, abuso de substâncias e morte por suicídio ou arritmias cardíacas 5,7,12,13,14,37,42,61,80 . O tratamento requer uma abordagem individualizada, a longo prazo e multidisciplinar.…”
Section: Comportamentos Alimentares Inadequadosunclassified
“…Up to one third of these deaths, including those occurring during re-feeding, are said to be due to cardiac causes but no precise data exist on SCD. Prolonged periods of starvation result in not only anatomical abnormalities such as cardiac muscle atrophy and pericardial effusions (582), but also ECG abnormalities, including sinus bradycardia and prolongation of the QTc interval, an effect that is likely to be compounded by the presence of concurrent electrolyte disturbances (582)(583)(584). SCD is therefore a frequent cause of mortality in this cohort.…”
Section: Zipes Et Al Acc/aha/esc Practice Guidelines E427mentioning
confidence: 99%